Improvement in Machining Rate with Mixed Electrolyte in ECDM Process. (2016) - Paul, Lijo; Hiremath, Somashekhar S.
Abstract: Electro Chemical Discharge Machining is one of the hybrid non-conventional machining process and it has wide scope for making intricate shapes in non-conducting materials. The mechanism of material removal in ECDM is thermal spark erosion (EDM) and chemical etching (ECM). Most of the researchers have used different base electrolytes – NaOH, KOH, NaCl etc for machining in ECDM process. In this paper an attempt has been made to machine a semi conducting engineering material with a mixed electrolyte of NaOH and KOH. Results have shown the improvement in machining rate in terms of material removal rate with mixed electrolyte.